The collective [videorecording (DVD)] - Johnson, Don, 1950-; Rose, Ruby, 1986-; Tyrese (Quiver Distribution, 2023)
A young recruit to a mysterious agency of assassins finds himself going rogue on his first assignment, tracking down a dangerous group of human traffickers.